A10 AN ULCERATIVE COLITIS ESCHERICHIA COLI PATHOBIONT COLONIZES THE INTESTINAL MUCOSA OF SUSCEPTIBLE HOSTS AND PROMOTES COLITIS VIA HEMOLYSIN PRODUCTION. (1st March 2018) - Yang, H; Mirsepasi-Lauridsen, H C; Bosman, E S; Struve, C; Yu, H; Wu, X; Ma, C; Reid, G; Li, X; Petersen, A M; Jacobson, K; Krogfelt, K A; et al.
Abstract: Background: Ulcerative colitis (UC) and Crohn's disease (CD) are chronic inflammatory conditions of the gastrointestinal (GI) tract that have been linked to intestinal microbial dysbiosis. While adherent-invasive Escherichia coli are associated with CD, recent studies have identified E. coli of phylogroup B2 as being frequently isolated from UC patients. B2 E. coli isolated from UC patients (such as p19A) harbour extra-intestinal pathogenic E. coli virulence factors including alpha hemolysin genes (hlyI, II). Correspondingly, the p19A strain causes cell death and barrier dysfunction in human epithelial colorectal cell lines, however its role in intestinal immunopathology is unclear because of the lack of a suitable animal model. Aims: The current study explores the potential to establish a mouse model of GI infection by the UC-associated E. coli strain p19A, as well as defines the mechanisms by which it promotes colitis. Methods: C57BL/6 and Sigirr (Single Ig IL-1R-related Receptor) deficient mice were orally administered with 5 mg vancomycin 6 hours prior to the oral infection with 10 8 colony forming units (CFU) of P19A. Sigirr -/- mice were examined because they show increased susceptibility to infection by enteric bacterial pathogens. Intestinal tissues as well as feces were homogenized and plated to enumerate CFU. An in vivo imaging system visualized the colonization of p19A in the intact intestines. To test the impact of pre-existing p19A colonization on experimental colitis, mice were colonized with DH10B (non-pathogenic E. coli control), p19A wild-type strain or p19A-ΔhlyI, II (a mutant strain lacking hemolysin genes). The next day, mice were given 3% (wt/vol) dextran sulfate sodium (DSS) in their drinking water for 4 days. Mice were monitored daily and euthanized to collect samples for further analysis. Results: Vancomycin pretreatment led to persistent p19A colonization of the intestinal lumen of C57BL/6 mice, based on luciferase based imaging and fecal shedding data. Furthermore, p19A colonized the intestinal mucosal surface of Sigirr -/- mice. While p19A infection caused only minimal pathology on its own, it dramatically worsened the course of DSS colitis, in concert with deep penetration of the damaged colonic mucosa. Notably, a p19A strain deficient in hemolysin genes was severely attenuated in its ability to promote DSS colitis in Sigirr -/- mice. Conclusions: Our findings provide evidence that a UC E. coli pathobiont can readily and persistently colonize the intestines of susceptible hosts, and significantly worsen the course of colitis. This model thus facilitates research into the role played by UC associated E. coli pathobionts in the pathogenesis of IBD. Funding Agencies: CCC, CIHRNSERC, MITACs, and CHILD Foundation